TEACHERS' AND STUDENTS' PERCEPTION TOWARDS DEEP LEARNING PARADIGM WITHIN ICT IN ELT AT SMA N 2 PEMATANGSIANTAR - Reza Sanjaya Sinaga; Tiarma Intan Marpaung; David Berthony Manalu (RADJA PUBLIKA, 2025)
The rapid integration of Information and Communication Technology (ICT) in education has prompted a paradigm shift in English Language Teaching (ELT), including the implementation of the Deep Learning framework introduced by the Indonesian Ministry of Education in 2024. This study aims to explore teachers’ and students’ perceptions toward the application of the Deep Learning paradigm within ICT-supported ELT at SMA Negeri 2 Pematangsiantar. A qualitative survey design was employed, involving interviews with two English teachers and questionnaires distributed to 109 eleventh-grade students. The findings reveal that both teachers and students generally hold positive perceptions toward the Deep Learning approach, particularly in the dimensions of mindful, meaningful, and joyful learning. Teachers perceive the paradigm as a refinement rather than a novel concept, although their understanding of its principles varies. Questionnaire results indicate high levels of agreement across the three dimensions: Joyful Learning (87.16%), Meaningful Learning (85.57%), and Mindful Learning (84.59%). However, several challenges emerged, including students’ limited metacognitive awareness, low confidence in applying English in real contexts, and passive participation during classroom activities. ICT was perceived as an essential tool that enhances engagement, supports assessment practices, and increases learning motivation, though its pedagogical application remains predominantly surface-level. Overall, the study concludes that the Deep Learning paradigm, when supported by ICT, positively influences learning experiences in ELT and demonstrates potential as an effective instructional approach. Strengthening teacher training and developing ICT-based instructional strategies are recommended to optimize implementation and foster deeper learning outcomes.